Transforming educational space under the impact of the pandemic: student and teacher well-being in higher education - L. V. Kozhevnikova; I. E. Starovoytova; A. V. Shishkova (Вестник университета)
The article presents the study of some areas of educational space transformation under the COVID-19 pandemic influence. The focus of attention is on such problems as the cognitive well-being of the student, the tutor model of teacherstudent relations in the digitalising educational space, the functioning of academic mobility institution in a pandemic and post-pandemic world. Cognitive well-being of students implies mastering digital literacy with strict adherence to the norms of digital ethics. A tutor in modern education plays the role of not only a developer of an individual educational trajectory, but also a controller and educator. For the successful implementation of tutoring functions, the teaching staff of universities needs additional training. The main trends in academic mobility are internal and virtual mobility. The authors conclude that educational organisations need for adequate infrastructural policy, and educational space – inevitable transformations in budget financing. The results of the article can be used in further research on the higher education transformation problems, in the development of proposals and recommendations for specialists in the of higher education management field for use in practice.